O impacto da rosuvastatina no remodelamento cardíaco pós infarto agudo do miocárdio em ratas - Fernandes, Daniella Marques (2021)
Introduction: Acute myocardial infarction (AMI) is one of the main causes of death in postmenopausal women. There is a direct relationship between estrogen reduction, dyslipidemia, low-intensity chronic inflammation, development of cardiovascular disease, and worse cardiac remodeling after AMI in women. Statins reduce long-term cardiovascular events. Some types of statins, such as rosuvastatin, have pleiotropic effects and can improve autonomic balance and reduce the vascular and systemic inflammatory process, especially in males. There is little information about the pleiotropic effects of statins on autonomic modulation and cardiac remodeling after AMI in estrogen-deprived or non-estrogenic female rats. Objectives: To evaluate the effects of Rosuvastatin on the sympathovagal balance and morphofunctional changes of the heart after AMI in ovariectomized rats. Methods: Female Rattus norvegicus of the Wistar lineage, 8-10 weeks old, were randomly divided into four groups: intact, intact and infarcted, ovariectomized, and ovariectomized and infarcted. Each group was subdivided into two others: placebo and treated with rosuvastatin. Bilateral oophorectomy was performed by direct removal of the ovaries after an abdominal incision (day 1 of the protocol); AMI was obtained by direct ligation of the left coronary artery, after thoracotomy (day 7); rosuvastatin was administered at a dose of 0.15 mg/kg/day, for 30 days, administered by gavage 1x day, started 48 hours before the AMI (day 5). Cannulation of the femoral artery was performed (day 34) to record blood pressure curves (day 35), and subsequent analysis of autonomic variables (baroreflex sensitivity, heart rate variability and blood pressure) and echocardiographic study to obtain morphofunctional parameters of the heart (day 35). Statistical analysis: we analyzed the effect of rosuvastatin under three conditions: in female rats with normal (intact) estrogens; rats with reduced estrogen (ovariectomized), and mimicking a life cycle. Data normality was tested with the Shapiro Wilk test. For comparison between groups, the east of repeated measures ANOVA was used, followed by Tukey's post hoc test. Results: were presented as mean and standard deviation; differences were considered statistically significant when p<0.05. Results: The data obtained in the analysis of the reduced estrogen condition (ovariectomized females) demonstrated the autonomic modulation through the reduction of baseline parameters such as systolic blood pressure (SBP) and mean arterial pressure (MAP). In addition, we were able to infer an improvement in baroreflex sensitivity, restoring the deleterious effects to cardiovascular reflex control after infarction. As expected, AMI caused an enlargement of the left ventricle and a reduction in its systolic function. The analysis of the condition of normal estrogen (intact) and reduced estrogen (ovariectomized) showed that treatment with rosuvastatin in females with or without AMI did not modify the morphofunctional parameters of the heart. Conclusion: The present study allows us to conclude that the effects of treatment with Rosuvastatin can modulate basal parameters such as SBP and MBP in ovariectomized and infarcted rats, improve baroreflex sensitivity, but it does not improve the morphofunctional functions of the heart after AMI in ovariectomized rats .